Perioperative Management of the Ambulatory Anorectal Surgery Patient - Shaw, Darcy; Ternent, Charles A. (Clinics in Colon and Rectal Surgery, 2016)
Ambulatory surgery is appropriate for most anorectal pathology. Ambulatory anorectal surgery can be performed at reduced cost compared with inpatient procedures with excellent safety, improved efficiency, and high levels of patient satisfaction. Several perioperative strategies are employed to control pain and avoid urinary retention, including the use of a multimodal pain regimen and restriction of intravenous fluids. Ambulatory anorectal surgery often utilizes standardized order sets and discharge instructions.
Keywords: ambulatory surgery; anorectal surgery; outpatient surgery